2020
DOI: 10.3389/fphys.2019.01591
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Resistance Mechanisms of Synthetic Insecticides and Botanicals, Phytochemicals, and Essential Oils as Alternative Larvicidal Agents Against Mosquitoes

Abstract: Mosquitoes are a serious threat to the society, acting as vector to several dreadful diseases. Mosquito management programes profoundly depend on the routine of chemical insecticides that subsequently lead to the expansion of resistance midst the vectors, along with other problems such as environmental pollution, bio magnification, and adversely affecting the quality of public and animal health, worldwide. The worldwide risk of insect vector transmitted diseases, with their associated illness and mortality, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(95 citation statements)
references
References 216 publications
3
88
0
4
Order By: Relevance
“…The sub-lethal dosage of My-It statistically reduced the oviposition deterrence index of the dengue mosquito at 1 × 10 4 conidia/mL with maximum deterrence index of 83.4% (F4,20 = 25.88, p ≤ 0.001) and it is more significant than those of the other treatments-1 × 10 4…”
Section: Oviposition Deterrence Indexmentioning
confidence: 87%
See 2 more Smart Citations
“…The sub-lethal dosage of My-It statistically reduced the oviposition deterrence index of the dengue mosquito at 1 × 10 4 conidia/mL with maximum deterrence index of 83.4% (F4,20 = 25.88, p ≤ 0.001) and it is more significant than those of the other treatments-1 × 10 4…”
Section: Oviposition Deterrence Indexmentioning
confidence: 87%
“…Larvicidal bioassays were adapted based on the methodology of the World Health Organization [4] with slight modifications. The second, third, and fourth instar larvae were transferred into 250 mL sterile plastic containers covering 25 mL of dosage treatments with different discriminate concentration of My-It (1 × 10 2 , 1 × 10 4 , 1 × 10 6 , and 1 × 10 8 conidia/mL) with the blend of 24 mL de-chlorinated sterile water, along with 1 mL of mycotoxin dosage, and kept at 27 • C. This procedure was replicated three times and one control was kept for each replication, i.e., 20 larvae were used without any chemicals.…”
Section: Larvicidal Bioassaymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that insecticide use has detrimental effects on non-target organisms, for example imidacloprid on honey bee ( Apis mellifera ) [ 17 ], damselfly ( Ischnura senegalensis ) [ 18 ], fathead minnow ( Pimephales promelas ), or the amphipod ( Hyalella azteca ) [ 19 ]. Thus, there is a need for new and complementary methods for controlling insect vectors, and essential oils have shown promise as renewable and environmentally-safe alternatives to the use of synthetic insecticides [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Lamiaceae has been an important family in terms of biologically active essential oils. Essential oils from members of this family have demonstrated potential as natural insect pest control agents [ 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The genus Premna L. was formerly included in the family Verbenaceae, but has been reassigned to the Lamiaceae [ 33 ].…”
Section: Introductionmentioning
confidence: 99%